"A hundred visions and revisions": Malone's annotations to Johnson's Dictionary - Iamartino, G (2010)
Researchers on Samuel Johnson's Dictionary have carefully analysed the lexicographer's methodology and expanded on the technicalities of his compilation, with regard to both the first edition of 1755 and the fourth, revised edition of 1773. The early reception and criticism of the Dictionary have also been studied, especially as far as the awkwardness and idiosyncrasy of some of Johnson's definitions are concerned. Annotated copies of the Dictionary, instead, represent a still neglected, undervalued research area in Johnsonian studies, and undeservedly so, since they may both furnish detailed lexicographical critcism and represent privileged dictionary users' viewpoint, and can therefore offer us reliable and interesting data on the way Johnson's lexicographical achievement was received by the cultural élite of this times. Following my previous research on Samuel Dyer's annotated copy of the Dictionary (which, when the scholar died in 1772, passed to Edmund Burke, who added his own notes), it is the purpose of my paper to present the work of another annotator of the Dictionary, i.e., Edmond Malone, the renowned Shakespearian scholar and member of Johnson's circle; beginning in November 1808, Malone added some 3000 notes in his copy of the Dictionary, and made lists of 'Modern Quoted' and 'English Idioms'. I will carry out a quantitative and qualitative analysis of Malone's notes, and will outline a taxonomy of his addenda and corrigenda to the Dictionary. My paper is therefore meant to contribute to a deeper knowledge of the Dictionary itself and, on a methodological level, to the research into the interplay between language data, lexicographic technique and cultural tenets in an epoch-making dictionary.